2015
DOI: 10.3109/00952990.2015.1043738
|View full text |Cite
|
Sign up to set email alerts
|

Review of hookah tobacco smoking among college students: policy implications and research recommendations

Abstract: Background: About 30% of college students have smoked hookah tobacco. Although most students perceive this product to be innocuous and non-addictive, hookah tobacco increases the risk for disease and nicotine dependence. Currently, the US Food and Drug Administration (FDA) does not regulate the manufacture, distribution, or sale of hookah tobacco. Objective: Empirical literature pertaining to hookah tobacco smoking is reviewed with a focus on the implications for regulatory policy. Methods: PubMed, PsycINFO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…Studies on cigarettes showed adolescents and young adults were likely to reduce tobacco use when prices increase. 59,60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on cigarettes showed adolescents and young adults were likely to reduce tobacco use when prices increase. 59,60 …”
Section: Discussionmentioning
confidence: 99%
“…Limiting the number of lounges per city, thereby reducing the density of lounges within certain geographic areas, may strengthen this barrier to visiting lounges. 59 Zoning ordinance regulators are encouraged to address the phenomena of the high density of lounges within their cities as an approach to reducing the spread of lounges.…”
Section: Discussionmentioning
confidence: 99%
“…Most available studies on hookah smoking in the United States have been conducted among subgroups such as college students (Barnett, Smith, et al, 2013; Enofe, Berg, & Nehl, 2014; Gathuru, Tarter, & Klein-Fedyshin, 2015; Shepardson & Hustad, 2015), youth (Lauterstein, et al, 2014; Wang, King, Corey, Arrazola, & Johnson, 2014), and young adults (Rezk-Hanna, Macabasco-O'Connell, & Woo, 2014; Sutfin, Song, Reboussin, & Wolfson, 2014). Few recent studies have documented the prevalence of hookah smoking and examined the factors associated with it among a nationally representative sample of U.S. adults (Agaku, et al, 2014; McMillen, Maduka, & Winickoff, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the onset of Hookah use happens at a later time, after the individuals had contact with alcohol, marijuana or cigarette (2,10,20) and is frequently associated with alcoholic drinks consumption. (19,21) Our study found that alcoholic drinks consumption is around three times higher among Hookah smokers when compared to non-smokers. At a longitudinal study performed with 936 university students from the New York region (USA) and surroundings, around 96% of Hookah users reported the current use of alcohol compared to 61% of non-smokers.…”
Section: Discussionmentioning
confidence: 66%